Broken Tax Breaks? Evidence from a Tax Credit Information Experiment with 1,000,000 Students - Peter Bergman; Jeffrey T. Denning; Dayanand Manoli (Institute of Labor Economics (IZA), 2017)
There is increasing evidence that tax credits for college do not affect college enrollment. This may be because prospective students do not know about tax benefits for credits or because the design of tax credits is not conducive to affecting educational outcomes. We focus on changing the salience of tax benefits by providing information about tax benefits for college using a sample of over 1 million students or prospective students in Texas. We sent emails and letters to students that described tax benefits for college and tracked college outcomes. For all three of our samples – rising high school seniors, already enrolled students, and students who had previously applied to college but were not currently enrolled – information about tax benefits for college did not affect enrollment or reenrollment. We test whether effects vary according to information frames and found that no treatment arms changed student outcomes. We conclude that salience is not the primary reason that tax credits for college do not affect enrollment.
Keywords: I22; I23; H2; 330; tax benefits for college